Dual inhibition of enhancer of zeste homolog 1/2 overactivates WNT signaling to deplete cancer stem cells in multiple myeloma. Issue 1 (16th November 2018) - Nakagawa, Makoto; Fujita, Shuhei; Katsumoto, Takuo; Yamagata, Kazutsune; Ogawara, Yoko; Hattori, Ayuna; Kagiyama, Yuki; Honma, Daisuke; Araki, Kazushi; Inoue, Tatsuya; Kato, Ayako; Inaki, Koichiro; et al.
Abstract : Multiple myeloma (MM) is an incurable hematological malignancy caused by accumulation of abnormal clonal plasma cells. Despite the recent development of novel therapies, relapse of MM eventually occurs as a result of a remaining population of drug‐resistant myeloma stem cells. Side population (SP) cells show cancer stem cell‐like characteristics in MM; thus, targeting these cells is a promising strategy to completely cure this malignancy. Herein, we showed that SP cells expressed higher levels of enhancer of zeste homolog ( EZH ) 1 and EZH2, which encode the catalytic subunits of Polycomb repressive complex 2 (PRC2), than non‐SP cells, suggesting that EZH1 as well as EZH2 contributes to the stemness maintenance of the MM cells and that targeting both EZH1/2 is potentially a significant therapeutic approach for eradicating myeloma stem cells. A novel orally bioavailable EZH1/2 dual inhibitor, OR‐S1, effectively eradicated SP cells and had a greater antitumor effect than a selective EZH2 inhibitor in vitro and in vivo, including a unique patient‐derived xenograft model. Moreover, long‐term continuous dosing of OR‐S1 completely cured mice bearing orthotopic xenografts. Additionally, PRC2 directly regulated WNT signaling in MM, and overactivation of this signaling induced by dual inhibition of EZH1/2 eradicated myeloma stem cells and negatively affected tumorigenesis, suggesting that repression of WNT signaling by PRC2 plays an important role in stemness maintenance of MM cells. Our results show the role of EZH1/2 in the maintenance of myeloma stem cells and provide a preclinical rationale for therapeutic application of OR‐S1, leading to significant advances in the treatment of MM. Abstract : Long‐term continuous administration of OR‐S1 completely cured all mice bearing orthotopic xenografts without eliciting any serious side‐effects. We confirmed this result by counting minimal residual cells by flow cytometric analysis. These results suggest that long‐term continuous administration of OR‐S1 impairs the self‐renewal activity of myeloma stem cells, rendering these cells unable to reconstitute disease and leading to the complete cure of MM.